Lung clearance of Staphylococcus aureus strains with differing protein A content: protein A effect on in vivo clearance. - Gross, G N (1978)
We have studied the clearance from murine lungs of two strains of Staphylococcus aureus, one possessing high and the other possessing low levels of protein A.S. aureus FDA 209 and S. aureus Wood 46 were assayed for their ability to bind mouse immunoglobulin G, using an indirect radioimmunoassay. S. aureus FDA 209 binding of mouse immunoglobulin was significantly greater than that of S. aureus Wood 46 (118,909 versus 37,845 cpm). Clearance of these two strains from the lung after a 30-min aerosol inoculation period was not significantly different. The percentage of bacteria remaining in the lung was 49.2 and 55.0% at 2h, 31.8 and 33.2% at 3 h, and 25.4 and 17.2% at 4 h for protein A-rich and protein A-poor strains, respectively (P greater than 0.20 at each time). These data suggest that the previously demonstrated in vitro antiphagocytic effect of protein A may not be relevant to pulmonary clearance mechanisms.